Adaptation of unbiased stereological methods to study theeffects of feed composition on the morphometrics of the different layers of the digestive tract of juvenile Atlantic cod (Gadus morhua L.) - Pindard, Lars Erik (The University of Bergen, 2004)
Juveniles of Atlantic cod (Gadus morhua L.) were fed food, containing different compositions of macro-nutrients (proteins, fat and carbohydrates). The aims of this study were to evaluate the use of unbiased stereology to find out if there were any differences in estimated weight, volume and/or total surface area and to describe a general digestive tract in these juvenile cod. By employing Technovit 7100 as embedding medium, it was possible to apply a VUR (vertical uniform random) sampling protocol and obtain samples unbiased. Hits from a point-counting grid were used to calculate estimations of volume fraction, and hits from a cycloid counting grid were used for calculating estimations of total surface area of the digestive tract. The estimations showed that there were no significant differences between any of the tested food types in any of the calculated parameters, apart from one, found in the estimated surface ratio of the intestine. This may, however, be due to high variability present in the material. There were no differences between diet groups, regarding thelayers of the digestive tracts whatever diet the fish were given, and the description of the layers in the digestive tract, supports previous findings.